Saṃvidhāna ra pañcāyata kānūna : pāṭhyāṃśa saṅkhyā 112 kā nimitta - Pradhāna, Gajendramaṇi, 1938- (Pāṭhyakrama Vikāsa Kendra, Tribhuvana Viśvavidyālaya, 1981)
On Nepal's constitution and laws on panchayat system of government.